Board authority culture, cultural diversity and corporate innovation - Kun Luo; Tianyu Gao; Yixin Li (China Journal of Accounting Studies (CJAS), 2023)
Culture is the core factor of corporate innovation, and board culture is the core embodiment of cultural factors in corporate governance. Board culture will have an important impact on corporate innovation, So what kind of board culture can Chinese boards build to better contribute to corporate innovation? Based on this core issue, this paper empirically explores the relationship between board authority culture, board cultural diversity and corporate innovation from the unique perspective of board culture. The results show that board authority culture is negatively related to corporate innovation; board cultural diversity can negatively regulate the relationship between board authority culture and corporate innovation, that is, the construction of diverse board culture of the Chinese board is more conducive to corporate innovation. The main reason why board authority culture inhibits corporate innovation is that board authority culture has obedience effect and inhibits corporate innovation through the path of increasing agency costs and weakening management risk preferences. Further research finds that the negative moderating effect of board culture diversity on the relationship between board authority culture and corporate innovation is more effective when the chairman has the highest authority directorship and has reputation authority but not political resource authority and organisation authority.
Keywords: 650; Board authority culture; board cultural diversity; corporate innovation; obedience effect